PENGARUH DANA PIHAK KETIGA, CAPITAL ADEQUACY RATIO, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS - Asri, Ni Nyoman Sri; Suarjaya, Anak Agung Gede (E-Jurnal Manajemen, 2018)
ABSTRACT  Profitability is a company's ability to earn profits in a certain period. This study aims to analyze  the  influence  of third party funds (DPK), capital adequacy ratio (CAR), liquidity (loan to deposit ratio), and company size on the profitability of LPD in Gianyar Regency. This research  was conducted on all LPDs in Gianyar Regency in 2016. The number of samples used was 149 LPD through probability sampling method with simple random rampling technique. This research uses non participant observation  method and using multiple linear regression analysis. Based  on the results of this research analysis shows that  partially DPK has  a  significant positive effect  on return on assets in LPD in Gianyar regency. CAR  partially  significant positive   effect on ROA in Gianyar Regency LPD. Loan to deposit ratio partially have a significant positive effect on ROA in LPD of Gianyar Regency. The size of the Company partially has no significant effect on ROA in LPD of Gianyar Regency. Keywords: DPK, CAR, Liquidity, Company Size, Profitability. ABSTRACT   Profitability is a company's ability to earn profits in a certain period. This study aims to analyze  the  influence  of third party funds (DPK), capital adequacy ratio (CAR), liquidity (loan to deposit ratio), and company size on the profitability of LPD in Gianyar Regency. This research  was conducted on all LPDs in Gianyar Regency in 2016. The number of samples used was 149 LPD through probability sampling method with simple random rampling technique. This research uses non participant observation  method and using multiple linear regression analysis. Based  on the results of this research analysis shows that  partially DPK has  a  significant positive effect  on return on assets in LPD in Gianyar regency. CAR  partially  significant positive   effect on ROA in Gianyar Regency LPD. Loan to deposit ratio partially have a significant positive effect on ROA in LPD of Gianyar Regency. The size of the Company partially has no significant effect on ROA in LPD of Gianyar Regency. Keywords: DPK, CAR, Liquidity, Company Size, Profitability.